IMPLEMENTATION OF THE POLICY OF PROCUREMENT OF GOODS AND SERVICES THROUGH E-PURCHASING WITHIN THE MEDAN CITY GOVERNMENT - Dian Mayasari Manurung; Adam Adam; Beby Masitho Batubara (SOSIOEDUKASI, 2026)
This study aims to analyze the implementation of the policy of procurement of goods and services through the e-purchasing system within the Medan City Government, focusing on the effectiveness of policy implementation, the level of compliance of regional apparatus, and the obstacles faced in its implementation. The research uses a qualitative approach with a descriptive-analytical method. The data was collected through in-depth interviews with officials of the Goods/Services Procurement Work Unit (UKPBJ), Commitment Making Officials (PPK), and related regional apparatus, complemented by documentation studies on regulations, procurement reports, and e-purchasing transaction data. Data analysis is carried out through the stages of data reduction, data presentation, and systematic conclusion drawn. The findings of the study show that the implementation of the e-purchasing policy in the Medan City Government in general has been running in accordance with the provisions of laws and regulations and contributes to increasing transparency, time efficiency, and accountability in the procurement process of goods and services. However, this study also found a number of obstacles, including limited human resource competence, suboptimal use of electronic catalogs, and resistance of some apparatus to changes from conventional procurement systems to digital. The results of the study confirm that the success of the implementation of e-purchasing is not only determined by the readiness of the technology system, but also by institutional capacity, organizational commitment, and continuous support through training and supervision. This study recommends strengthening human resource capacity and optimizing electronic catalog management as a strategic step in increasing the effectiveness of e-purchasing policies within the Medan City Government.